Os problemas de saúde mental na visão do agente comunitário de saúde do Município de Praia Grande-SP - Sousa, Lucélia Santos (2012)
Million people around the world are affected by mental health problems and they aren¿t assisted as expected. Studies show relevant points about mental health care in the primary assistance. Some of these studies talk about the Family Health Program, but in special the job of the community health worker as an important and meaningful strategy in the assistance to the mental disordered patients and its family. However, the lack of preparation of these professionals in dealing with situations related to mental health is remarkable. Starting from this approach the following task comes from an interest in contributing to a reflection about the necessary support that the community workers need to cooperate in the assistance to the community patients with mental health problems. The study aims to understand the vision of the community workers about mental health problems. This is about the qualitative research methods composed by traditional research techniques of anthropology: dense ethnographic observation and depth interviews with 15 agents from a primary care unity of Praia Grande city in São Paulo. The field research was done from March to June 2011. The narratives of each agent interviewed make possible to identify the representation about mental health problems. A common aspect of the reports was noted, the trust relationship between the person with some mental problem and the community worker. Mental disorders are identified through the records of the family conversations held at home or in the clinic and through the relatives and neighbor¿s report. The concern about mental health problems is related to the bond established with her own family, with real cases in this activity area and with some courses made. The notion of mental health problem had many meanings, and there was a concern to not confuse them with crazy people. The reasons given mentioned an past or present event: stress, financial and life condition, alcohol abuse, drug abuse, family and genetic problems. Was concluded that community workers need information and specific training about mental health to face this situations in their daily work. Furthermore the relationship established between these people and the patients and their families to give subsidy to build interventions about mental health.